Residual feed intake phenotype and gender affect the expression of key genes of the lipogenesis pathway in adipose tissue of beef cattle - Porter, Richard (My University, 2018)
Background: Feed accounts for up to 75% of costs in beef production systems, thus any improvement in feed efficiency (FE) will benefit the profitability of this enterprise. Residual feed intake (RFI) is a measure of FE that is independent of level of production. Adipose tissue (AT) is a major endocrine organ and the primary metabolic energy reservoir. It modulates a variety of processes related to FE such as lipid metabolism and glucose homeostasis and thus measures of inter-animal variation in adiposity are frequently included in the calculation of the RFI index. The aim of this study was to determine the effect of phenotypic RFI status and gender on the expression of key candidate genes related to processes involved in energy metabolism within AT. Dry matter intake (DMI) and average daily gain (ADG) were measured over a period of 70 d for 52 purebred Simmental heifers (n = 24) and bulls (n = 28) with an initial BW±SD of 372±39.6 kg and 387±50.6 kg, respectively. Residual feed intake was calculated and animals were ranked within gender by RFI into high (inefficient; n = 9 heifers and n = 8 bulls) and low (efficient; n = 9 heifers and n = 8 bulls) groups. Results: Average daily gain ±SD and daily DMI ±SD for heifers and bulls were 1.2±0.4 kg and 9.1±0.5 kg, and 1.8±0.3 kg and 9.5±1 kg respectively. High RFI heifers and bulls consumed 10% and 15% more (P < 0.05) than their low RFI counterparts, respectively. Heifers had a higher expression of all genes measured than bulls (P < 0.05). A gender × RFI interaction was detected for HMGCS2(P < 0.05) in which high RFI bulls tended to have lower expression of HMGCS2 than low RFI bulls (P < 0.1), whereas high RFI heifers had higher expression than low RFI heifers (P < 0.05) and high RFI bulls (P < 0.05). SLC2A4 expression was consistently higher in subcutaneous AT of low RFI animals across gender. Conclusion: The findings of this study indicate that low RFI cattle exhibit upregulation of the molecular mechanismsgoverning glucose metabolism in adipose tissue, in particular, glucose clearance. The decreased expression ofSLC2A4in the inefficient cattle may result in less efficient glucose metabolism in these animals. We conclude thatSLC2A4maybe a potential biomarker for RFI in cattle.
PUBLISHED
Keywords: Adipose; Cattle; RFI; SLC2A4; Genes & Society; genetics and genomics; Other